2020
DOI: 10.1645/19-75
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Reveals New Insights into the Allergomes of Anisakis simplex, Pseudoterranova decipiens, and Contracaecum osculatum

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…Additionally, the similar reaction to ES proteins observed for both parasites would suggest a high similarity between Anisakis and Contracaecum IgE-epitopes, since specific anisakis -IgE generally reacts more specifically to these kind of proteins [ 5 , 27 , 28 , 29 ]. This fact would be also confirmed by the numerous Contracaecum protein bands that were revealed in the WB analysis, recognized by specific Anisakis IgE from sera in this work, and is in agreement with previous works by IgG-ELISA-based serodiagnosis [ 18 ] and by proteomic profiling [ 19 ] with both species. However, personal responses have not been studied in this work by in vitro methods, and it should be stated that the individual response against A. simplex and C. osculatum antigens could differ depending on the individual patients with allergic anisakidosis, as observed by in vivo methods.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, the similar reaction to ES proteins observed for both parasites would suggest a high similarity between Anisakis and Contracaecum IgE-epitopes, since specific anisakis -IgE generally reacts more specifically to these kind of proteins [ 5 , 27 , 28 , 29 ]. This fact would be also confirmed by the numerous Contracaecum protein bands that were revealed in the WB analysis, recognized by specific Anisakis IgE from sera in this work, and is in agreement with previous works by IgG-ELISA-based serodiagnosis [ 18 ] and by proteomic profiling [ 19 ] with both species. However, personal responses have not been studied in this work by in vitro methods, and it should be stated that the individual response against A. simplex and C. osculatum antigens could differ depending on the individual patients with allergic anisakidosis, as observed by in vivo methods.…”
Section: Discussionsupporting
confidence: 93%
“…In the last 20 years, it has become apparent that A. simplex is one of the most important hidden food allergens in the adult population suffering acute urticaria and anaphylaxis [ 30 ]. Regarding the results presented in this and previous works [ 19 ], and the practical lack of SPT-response from the other studied parasites from freshwater ( Tetracotyle sp., Apophallus sp. and Posthodiplostomum sp.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In 2017, Ludovisi et al showed that intraperitoneal infection of mice with live P. decipiens L3 could induce a mixed T helper type (Th) 1/Th2 response and make mice react (i.e., irritability and reduced activity) to a subsequent oral challenge with P. decipiens proteins 7 . An allergenic potential of P. decipiens was also supported by a proteomic study by Kochanowski, et al, who revealed the presence of at least eight A. simplex -like allergens in crushed P. decipiens extract and predicted another 28 putative allergens in both A. simplex and P. decipiens by use of high-resolution liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) 8 . Such LC–MS/MS method had also been previously applied by Carrera, et al who identified one shared allergen (Ani s 9) between both nematode species 9 .…”
Section: Introductionmentioning
confidence: 75%
“…The symptoms include nausea, vomiting, diarrhea, or an allergic reaction. These reactions are caused by chemical compounds found in the fish meat, which are produced by the parasite (Ivanovic et al 2017;Kochanowski et al 2020). Cases of anisakiasis that has been reported were mostly caused by A. simplex and A. pegrefii (Baird et al 2014;Aibinu et al 2019) meanwhile, those caused by A. typica are not yet widely known and receive relatively less attention, therefore, the zoonotic effect may also be underestimated (Umehara et al 2010).…”
Section: Discussionmentioning
confidence: 99%